Behavior, performance and quality of carcass and meat of steers produced in feedlots (Research, Society and Development, 2020)
It is known that in intensive production systems, cattle are divided into lots and are usually in paddocks, often in small spaces. In addition to providing adequate facilities, nutrition, and health to confined animals, concern for their comfort and well-being helps, and a lot in the production of animals and consequently quality meat. Therefore, the objective of this study was to evaluate the behavior, performance and quality of carcass and meat of steers reared under different confinement conditions. Total of 19 steers were used, divided into two treatments: covered stall with access to external area (BA) with 12 m²/animal and covered stall without access to external area (BF) with 3.6 m²/animal. Weighing and behavior analysis of the animals were carried out monthly. After slaughter, hot carcass weight was measured, carcass finishing and conformation scores were assigned, pH, temperature, fat and meat color, morphometric measurements on carcasses, fat thickness, area were measured rib eye and marbling of the Longissumus dorsi muscle. In the laboratory, samples collected underwent analysis of cooking losses, softness, pH, temperature, color, loss of exudate and water retention capacity. There was no difference in body weight between groups. For social behavior, there was no difference between treatments. For eating behavior, the activities of rumination and leisure on foot were performed more frequently by animals in the BF group than in BA, and there was a preference for animals in the BA group to perform these and other activities in the external area of ​​the stall, for the activities of feeding, rumination and leisure lying there was no difference between groups. The carcass and meat quality characteristics were not influenced by the different confinement conditions. We conclude that the supply of external area to the confined animals did not influence the quality of carcass and meat, however, it changed their behavior.